Efficient Test Compaction for Combinational Circuits Based on Fault Detection Count-Directed Clustering - El-Maleh, Aiman H. (2007)
Test compaction is an effective technique for reducing test data volume and test application time. In this paper, we present a new static test compaction technique based on test vector decomposition and clustering. Test vectors are decomposed and clustered for faults in an increasing order of faults detection count. This clustering order gives more degree of freedom and results in better compaction. Experimental results demonstrate the effectiveness of the proposed approach in achieving higher compaction in a much more efficient CPU time than previous clustering-based test compaction approaches.